Co-limitation of resources reveals adaptations of a tropical tree to heterogeneous environments along an elevational cline - Paudel, Indira; Rose, Kyle M. E.; Landhäusser, Simon M.; Jacobs, Douglass F. (Frontiers in Forests and Global Change, 2023)
Plant species often exhibit significant variation in functional traits in populations along elevational gradients to cope with varying stress conditions. While plant development has been assumed to be most limited by a single resource, growing evidence suggests the potential for interactions of co-limiting resources to impact plant performance. Here, we aimed to determine how light, nitrogen, and water availability influence the growth and physiology of different populations of koa (Acacia koa), a tree species of concern that occurs across a large elevational gradient in tropical Hawaii, USA. Populations from three seed sources [low (L), mid (M), and high (H) elevation] were grown in a controlled greenhouse experiment and exposed to co-limiting light, water, and nutrient (nitrogen) conditions. Light response, gas exchange, water status, resource use efficiency, nutrients and shoot non-structural carbohydrate concentrations, and growth and biomass allocation responses were quantified. We found that resource co-limitation sometimes interacted to determine responses of the measured parameters. In general, the low elevation (L) koa population was more sensitive to conditions where both moisture and nutrients were limiting, while the high elevation (H) koa population was more sensitive to conditions where either light and moisture or light and nitrogen were co-limiting. The M population performed well overall regardless of resource limitation. Our findings lend support to the theory that multiple resources limit growth and physiology of populations rather than the traditional view of a single resource limiting performance. Therefore, the possibility that multiple resource limitations drive population differences should be considered when developing population-based guidelines for forest and tree species restoration.